2013
DOI: 10.1093/humrep/det338
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs transfected into granulosa cells may regulate oocyte meiotic competence during in vitro maturation of mouse follicles

Abstract: This work was supported by a grant from the Korean Health Technology R&D Project, Ministry of Health & Welfare, Republic of Korea (A111539). None of the authors has any conflicts of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 49 publications
3
60
0
1
Order By: Relevance
“…Furthermore, in silico prediction showed that miR-451 may target genes such as TSC1, whose absence in the murine model causes POF (50); SPC25, which induces spindle misalignment in knockout murine models (51); and EREG (also known as epiregulin), which has also been tested as an inductor peptide for cumulus-oocytes in in vitro maturation protocols (52). In the murine model, it has also been found that miR-27a expression is increased in GCs from MII versus MI murine oocytes (53). These results are in accordance with our observations for hsa-miR-27b, a miR-27a homolog, which is expressed in higher amounts in GV FF than in MII FF.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in silico prediction showed that miR-451 may target genes such as TSC1, whose absence in the murine model causes POF (50); SPC25, which induces spindle misalignment in knockout murine models (51); and EREG (also known as epiregulin), which has also been tested as an inductor peptide for cumulus-oocytes in in vitro maturation protocols (52). In the murine model, it has also been found that miR-27a expression is increased in GCs from MII versus MI murine oocytes (53). These results are in accordance with our observations for hsa-miR-27b, a miR-27a homolog, which is expressed in higher amounts in GV FF than in MII FF.…”
Section: Discussionmentioning
confidence: 99%
“…The methods used for OFIVM have been modified from previous studies [16,17]. For the experiment of OFIVM, early stage pre-antral follicles were mechanically separated using a syringe needle.…”
Section: Ofivm and Estrogen Treatmentmentioning
confidence: 99%
“…NAs play an important role in ovarian development and function through regulating post-transcriptional gene expression (Baley and Li, 2012;Kim et al, 2013;Lei et al, 2010). miR-210 is one of the most studied hypoxia-inducible miRNAs (Cicchillitti et al, 2012), and accumulating evidence suggests an important role for miR-210 in cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%